Comparing the emergence of Echinochloa crus‐galli populations in different locations. Part II: similarities and threshold parameters. (17th March 2022) - Royo‐Esnal, Aritz; Onofri, Andrea; Taab, Alireza; Loddo, Donato; Necajeva, Jevgenija; Uludag, Ahmet; Synowiec, Agnieszka; Calha, Isabel M.; Lars, Andersson; Jensen, Peter K.; Uremis, Ilhan; Economou, Garifalia; et al.
Abstract: The variability in the emergence process of different populations was confirmed for two Echinochloa crus ‐ galli populations, one from Italy (IT) and the second from Norway (NO). Seeds were sown in 12 localities over Europe and the Middle East, and the emergence patterns of IT and NO were compared with those of several local populations at each location. Seeds of each population were sown in pots buried to the ground level. The base temperature ( T b ) for emergence was estimated by (1) analysing logistic models applied to the field emergence of IT and NO, and (2) a germination assay set in winter 2020 at constant temperatures (8, 11, 14, 17, 20, 26, 29°C) with newly collected seeds in 2019 from the same fields where IT and NO had previously been harvested in 2015. The logistic models developed for IT and NO in each location showed that the emergence pattern of IT was similar to that of the local populations in Poland, Italy, Spain, Turkey South and Iran, while NO fitted better to those in Sweden and Latvia. No germination was obtained for IT in a germination chamber, but the estimated T b with the logistic model was 11.2°C. For NO, the estimated T b was 8.8°C in the germination chamber and 8.1°C in the field. Results suggest that adaptation to local environmental conditions has led to inter‐population differences in T b and parameter estimates of thermal‐time models to predict the emergence of E. crus‐galli should only be used for populations with similar climatic and habitat conditions.